2020
DOI: 10.3390/nu12020490
|View full text |Cite
|
Sign up to set email alerts
|

Body Image, Emotional Eating and Psychological Distress among Bariatric Surgery Candidates in Israel and the United States

Abstract: Background: The present study aimed to examine the relations between body image dissatisfaction (BID) and psychological distress variables among bariatric surgery candidates from two distinct cultures in Israel and in the United States. Methods: A sample of consecutive pre-surgical bariatric candidates was recruited from a Bariatric Center in Israel (N = 114) and a Bariatric Center in the Unites States (N = 81). Body image dissatisfaction (BID-BSQ8), suicidal ideation (SBQ-R), depressive symptoms (PHQ-9), anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…That positive perception could then reinforce improvements in emotional eating and vice versa (Baker & Brownell, 2000). Following from those relationships, and suggested by previous research (Geller et al, 2020), change in body satisfaction might mediate relations between improvements in physical activity and emotional eating.…”
supporting
confidence: 66%
“…That positive perception could then reinforce improvements in emotional eating and vice versa (Baker & Brownell, 2000). Following from those relationships, and suggested by previous research (Geller et al, 2020), change in body satisfaction might mediate relations between improvements in physical activity and emotional eating.…”
supporting
confidence: 66%
“…As already mentioned, the theory was first proposed as a theory of obesity (Annunziato and Grossman, 2016; DiClemente and Delahanty, 2016; Marks, 2015). Several empirical studies and reviews have supported the obesity theory, for example, Jumbe et al (2017), Czepczor-Bernat et al (2020), Geller et al (2020) and Modrzejewska et al (2021). With a Chinese sample, Liu et al (2022) observed an inverted U-shaped relationship between happiness and BMI.…”
Section: The Origin Of the Theorymentioning
confidence: 89%
“…This 9-item depression module from the PHQ is rated on a 3-point Likert scale, with higher scores indicating greater depression. The PHQ-9 has previously been used for individuals with EDs [ 36 ], and its Hebrew translation has been validated for Israeli populations, including patients with EDs [ 40 ]. Internal consistency of the PHQ-9 self-report in this study is α = 0.92.…”
Section: Methodsmentioning
confidence: 99%